Synthesis, Characterization and Biological Activity of Some Transition Metals Complexes with Schiff Base Derived from 4-Amino-5-phenyl-4H-1,2,4-triazole-3-thiol and p-Methoxysalicyldehyde - M.A. Altalbawy, Farag; G. Mohamed, Gehad; I.A. Mohamed, Mohamed (Asian Journal of Chemistry, 2010)
The coordination behaviour of Schiff base with NOS donation sites, derived from condensation of 4-amino-5-phenyl-4H-1,2,4-triazole-3-thiol and p-methoxysalicyldehyde (H2L), transition metal ions namely Cr(III), Mn(II), Co(II) (Cl, ClO4), Ni(II) (Cl, ClO4), Cu(II) and Zn(II) are reported. The metal complexes are characterized based on elemental analyses, IR, 1H NMR, solid reflectance, magnetic moment, molar conductance and thermal analyses (TG, DTG and DTA). The ionization constants of the Schiff base under investigation as well as the stability constants of its metal chelates are calculated pH metrically at 25 ºC and ionic strength μ = 0.1 M in 50 % (v/v) ethanol-water mixture. The chelates are found to have trigonal bipyramidal [Co(II), Ni(II), Zn(II)], tetrahedral [Cr(III) and Mn(II)] and square planar [Cu(II)] geometrical structures. The ligand and its binary chelates are subjected to thermal analyses and the different activation thermodynamic parameters are calculated from their corresponding DTG curves to throw more light on the nature of changes accompanying the thermal decomposition process of these compounds. The synthesized ligands, in comparison to their metal complexes also were screened for their antibacterial activity against bacterial species (Escherichia coli and B. subtilis) and Fungi (A. niger, A. flavus, C. albicans and C. tropicalis). The activity data show that the metal complexes have antibacterial and antifungal activity more than the parent Schiff base ligand against one or more bacterial species.